Forgotten dust: following plasterboard for non-destructive circular economies - Rumo, Delphine (Frontiers in Sustainability, 2023)
The exploitative and unsustainable life of the building material plasterboard requires alternative economies. A non-destructive circular model is one way to open imaginaries for more sustainable constructions. In this paper I examine the end of life of plasterboard as an experimental case for discussing such an alternative approach. My focus is on the disposal of the material, including its demolition, removal from construction sites, recycling and landfilling. Three months of fieldwork in the south of Finland clarified the current state of plasterboard. I followed the material across two building sites, two recycling facilities and a landfill site, and visually exposed disposal practices and material states to show the entanglement of workers, materials and circular economy discourses. My findings outline that plasterboard reproduces a problematic circularity that merely focuses on waste management through recycling, doing little to decrease the need for raw gypsum extraction. I show how plasterboard in disposal conceptually disappears from current economic models, which fail to address a variety of opportunities for more sustainable construction. My empirical research exposes a different material reality that is concerned with small amounts of plasterboard. I argue that attending to plasterboard in disposal opens possibilities to imagine more ethical engagements with the material. The research highlights how gypsum crumbs and dust are unable to play a role in the current circular economy. However, end-of-life plasterboard makes the inadequacy of the material for circulation visible and can contribute to a debate on the diverse economies of construction.